Evaluation of Drying Characteristics of Selected Fishes in Dryers developed by ICAR-CIFT - Fasludeen, N. S.; Murali, S.; Samuel, Manoj P.; Ninan, George; Joshy, C. G. (Fishery Technology, 2018)
ICAR-Central Institute of Fisheries Technology, Cochin, has developed different types of dryers for improving the quality of dried fishes i.e. Solar tray dryer with electrical back up (hybrid), Solar tunnel dryer, Electrical dryer and Solar cabinet dryer with electrical back up (hybrid). Drying characteristics studies on selected fishes, mackerel (Rastrelliger kanagurta) (80% moisture content (MC) on wet basis (wb) and glassy perchlet (Ambassis spp.) (77% MC on wb), was conducted using the solar tray dryer with electrical back up (hybrid) dryer. The tempeature obtained inside the chamber during drying was 65oC. The solar tunnel dryer, electrical dryer and solar cabinet dryer with electrical back up (hybrid) was evaluated with fresh and salted sole fish (Cynoglossus semifasciatus) (77% MC). Solar tunnel dryer under normal atmospheric conditions attained 45°C temperature, Electrical dryer was operated at 65°C temperature and Solar cabinet dryer with electrical back up (hybrid) attained 70°C temperature. Among the CIFT dryers evaluated, electric dryer was found to yield lower moisture dry product. Also, fish dried under electrical dryer received highest overall acceptability in sensory evaluation study.